Cuidado domiciliar farmacêutico na doença renal crônica: revisão integrativa de literatura - Garcia, Camila Nogueira [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Chronic kidney disease is a public health problem. Patients with CKD are polymedicated patients, requiring special attention, the pharmacist being the holder of the knowledge of medicines is the most suitable professional for this. The present study identified and described the duties of the pharmacist during a home visit with the patient with chronic renal disease, aiming at improving the clinical practice of the pharmacist and the health team, providing subsidies for quality care aimed primarily at the safety of the patient. patient. Objective: To identify in the literature the proposed theme; classified articles included in the integrative revision according to the STROBE and COREQ instruments; identify the level of scientific evidence of each article included in the review. Method: An integrative review of literature with bibliographic search was done in the Scopus, PubMed Web of Science and Embase databases. The articles included were analyzed by the STROBE and COREQ instruments and classified according to the level of evidence. Outcome: A total of 637 documents were identified: 253 in SCOPUS; 198 in PUBMED; 100 on WEB OF SCIENCE; 86 at EMBASE. Firstly, the duplicates were identified, articles with title and abstract that did not contemplate the theme, were excluded. Three articles were included, a quantitative and qualitative article, a quantitative and a literature review, obtained studies with level of evidence VI and VII. Conclusion: It is concluded that based on the literature that the presence of the pharmacist in home visits is of extreme importance to improve the patient's medication adherence. It was also verified that there is a need for professional qualification, change in the daily routine of the pharmacist and also an adequate financial return.

A doença renal crônica é um problema de saúde pública. Pacientes com DRC são pacientes polimedicados, necessitando de uma atenção especial, o farmacêutico sendo detentor do conhecimento de medicamentos é o profissional mais indicado para isto. O presente estudo identificou e descreveu as atribuições do farmacêutico em visita domiciliar com o paciente portador de doença renal crônica, visando à melhoria da atuação da pratica clinica do farmacêutico e da equipe de saúde, proporcionando subsídios para uma assistência de qualidade visando prioritariamente a segurança do paciente. Objetivo: Identificar na literatura o tema proposto; classificar os artigos incluídos na revisão integrativa de acordo com os instrumentos STROBE e COREQ; identificar o nível de evidencia cientifica de cada artigo incluído na revisão. Método: Realizado uma revisão integrativa de literatura com busca bibliográfica nas bases de dados Scopus, PubMed Web of Science e Embase. Os artigos incluídos foram submetidos a análise dos instrumentos STROBE e COREQ e classificados quanto ao nível de evidencia. Resultado: Foram identificados um total de 637 documentos: 253 na SCOPUS; 198 na PUBMED; 100 na WEB OF SCIENCE; 86 na EMBASE. Primeiramente foram identificadas as duplicadas, os artigos com titulo e resumo que não contemplavam ao tema, foram excluídos. Três artigos foram incluídos, um artigo quantitativo e qualitativo, um quantitativo e uma revisão de literatura, obtiveram-se estudos com nível de evidencia VI e VII. Conclusão: Conclui-se que com base na literatura que a presença do farmacêutico nas visitas domiciliares é de extrema importância para melhorar a aderência medicamentosa do paciente. Verificou-se ainda que há necessidade de qualificação profissional, mudança da rotina diária do farmacêutico e também um retorno financeiro adequado.
Pharmacist home care in chronic kidney disease: integrative literature review
Keywords: Chronic renal insufficiency; Pharmaceutical care; Home visit; Insuficiência renal crônica; Cuidados farmacêuticos; Visita domiciliar